Analisis Teks Hadis tentang Poligami dan Implikasinya - Rahmi Syahriza (Institut Agama Islam Negeri (IAIN) Curup, 2018)
This study aims to find out the understanding of hadith textually and contextually about the permissibility and prohibition of polygamy and its implications. The method used is the method of mawdhu`iy (thematic) with a textual and contextual understanding approach. The results of the study conclude that, 1) there is no contradiction between the traditions that allow and prohibit, even both contain indications that polygamy may be carried out by fulfilling certain conditions and considering the benefits and disadvantages, 2) Prophet Muhammad tightened polygamy by expressing reasons and consideration of benefits and disadvantages. Even the Prophet explicitly answered the question of friends why the Prophet did not want to marry Ansar women for reasons of jealousy. This indicates that there is a psychological and emotional element of women that is the concern of the Prophet. Likewise when Ali was about to marry again, the Prophet explicitly stated that he did not want Fatimah to be hurt. This also indicates the psychological aspects that the Prophet considered not to allow Ali to polygamy, also need to consider psychological and emotional factors